2014
DOI: 10.1007/s00706-014-1287-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical, theoretical, and morphological studies of antioxidant fullerosteroids

Abstract: Four fullerosteroidal conjugates, previously confirmed to express two-to threefold better antioxidant activity in vitro than C 60 , were subjected to additional studies, including electrochemical, theoretical, and morphological examination. All tested compounds underwent reversible, diffusion-controlled reductions. A notable influence of the solvent properties on the reduction potential, the level of aggregation, and the lowest unoccupied molecular orbital (LUMO) energy was observed. Theoretical calculations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…ral products. [17,18,20,21] Gathering these two entities has allowed these conjugates to be more soluble than pristine [60]fullerene in aqueous medium as well as in organic solvents. [13,14] It has also been shown that certain structural modifications induced the change of biological response, giving compounds with a wide scope of biological activity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…ral products. [17,18,20,21] Gathering these two entities has allowed these conjugates to be more soluble than pristine [60]fullerene in aqueous medium as well as in organic solvents. [13,14] It has also been shown that certain structural modifications induced the change of biological response, giving compounds with a wide scope of biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18,20,21] Gathering these two entities has allowed these conjugates to be more soluble than pristine [60]fullerene in aqueous medium as well as in organic solvents. Thus, some studies have been published reporting on the antioxidant activity of fulleropyrrolidines endowed with an steroid unit, [20,21,27] the effect of steroid-fullerene adducts on sarcoplasmic reticulum (SR) Ca 2+ -ATPase and survival of human lung adenocarcinoma cancer A549 cells. [23] The synthetic methods for preparing hybrid steroid-fullerenes are based on the electrophilic character of C 60 , the most common reactions reported for the modifications of fullerenes being the cycloadditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, morphological characterization of self-organized structures of fullerene–steroid [26] and fullerene–peptide–steroid hybrids [25] in solution and in the solid state was studied by SEM. In our previous work [27], we described the synthesis and provided a thorough spectral characterization of a series of fulleropeptide tert -butyl esters ( 2 – 12 , Fig.…”
Section: Introductionmentioning
confidence: 99%